Successful use of transcranial magnetic stimulation in difficult to treat hypersexual disorder - Adarsh Tripathi; Amit Singh; Harpreet Singh; Sujita Kumar Kar (Wolters Kluwer Medknow Publications, 2016)
Hypersexual disorder has phenomenological resemblance with impulsive-compulsive spectrum disorders. Inhibitory repetitive transcranial magnetic stimulation (rTMS) over the supplementary motor area (SMA) has been found to be effective in the management of impulsive-compulsive behaviors. Inhibitory rTMS over SMA may be helpful in hypersexual disorder. We highlight here a case of hypersexual disorder (excessive sexual drive) who failed to respond adequately to the conventional pharmacological treatment and responded with rTMS augmentation.